ANALISIS PENGARUH FAKTOR SOSIAL DEMOGRAFI TERHADAP INTENSITAS PENGGUNAAN JAMINAN KESEHATAN BALI MANDARA DI KABUPATEN BULELENG - Yuli Bhestari, Intan; Sudibia, I Ketut; Marhaeni, AAIN (PIRAMIDA; Vol 12 No 1 (2016), 2016)
The low quality of public health, especially the poor caused by several factors, namely the lack of awareness to maintain physical health, environmental hygiene and unhealthy lifestyle, and financing to gain access to good health. This study aims to analyze; 1) the recipient perceptions JKBM to services JKBM, 2) analyze the influence of the distance of residence, education, household size and tenure of the income users JKBM, 3) analyze the influence of the distance of residence, education, family size, employment, and income to the intensity of use JKBM and 4) analyzing the income of the recipient JKBM role in mediating the effect of variable area of residence, education, household size and tenure of the intensity of use JKBM in Buleleng. Data collection methods used were interviews and questionnaires, with a number of respondents as many as 119 people. The analytical tool used is descriptive analysis and path analysis. The results of the analysis of the recipient’s perception JKBM JKBM to health services in low category, the perception is very satisfied with the intensity of use JKBM. Distance shelter, and education, and a significant positive effect on revenues. Education and income of a significant negative effect on the intensity of use JKBM. Revenue fully mediate between the distance of a place to stay on the intensity of use JKBM.
Keywords: JKBM; education; income; distance of residence.